Neurotoxic effects of AZT on developing and adult neurogenesis - Demir, Meryem; Laywell, Eric D. (Frontiers in Neuroscience, 2015)
Azidothymidine (AZT) is a synthetic, chain-terminating nucleoside analog used to treat HIV-1 infection. While AZT is not actively transported across the blood brain barrier, it does accumulate at high levels in cerebrospinal fluid, and subsequently diffuses into the overlying parenchyma. Due to the close anatomical proximity of the neurogenic niches to the ventricular system, we hypothesize that diffusion from CSF exposes neural stem/progenitor cells and their progeny to biologically relevant levels of AZT sufficient to perturb normal cell functions. We employed in vitro and in vivo models of mouse neurogenesis in order to assess the effects of AZT on developing and adult neurogenesis. Using in vitro assays we show that AZT reduces the population expansion potential of neural stem/progenitor cells by inducing senescence. Additionally, in a model of in vitro neurogenesis AZT severely attenuates neuroblast production. These effects are mirrored in vivo by clinically-relevant animal models. We show that in utero AZT exposure perturbs both population expansion and neurogenesis among neural stem/progenitor cells. Additionally, a short-term AZT regimen in adult mice suppresses subependymal zone neurogenesis. These data reveal novel negative effects of AZT on neural stem cell biology. Given that the sequelae of HIV infection often include neurologic deficits—subsumed under AIDS Dementia Complex (Brew, 1999)—it is important to determine to what extent AZT negatively affects neurological function in ways that contribute to, or exacerbate, ADC in order to avoid attributing iatrogenic drug effects to the underlying disease process, and thereby skewing the risk/benefit analysis of AZT therapy.